2020
DOI: 10.1038/s41598-020-78089-5
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Fatty acid synthase, a novel poor prognostic factor for acute lymphoblastic leukemia which can be targeted by ginger extract

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The indispensability of lipid metabolism has been suggested to be a promising therapeutic target. Targeting FA biosynthesis and FA oxidation has been attempted in preclinical and clinical investigations, and both have encouraging outcomes against malignancies of T cells ( 13 , 23 , 104 , 209 ). The direct inhibition of cancer progression by targeting lipid metabolism as well as alleviation of chemo- and immunotherapy response has been demonstrated by various investigations ( 104 , 129 , 209 , 217 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The indispensability of lipid metabolism has been suggested to be a promising therapeutic target. Targeting FA biosynthesis and FA oxidation has been attempted in preclinical and clinical investigations, and both have encouraging outcomes against malignancies of T cells ( 13 , 23 , 104 , 209 ). The direct inhibition of cancer progression by targeting lipid metabolism as well as alleviation of chemo- and immunotherapy response has been demonstrated by various investigations ( 104 , 129 , 209 , 217 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting FA biosynthesis and FA oxidation has been attempted in preclinical and clinical investigations, and both have encouraging outcomes against malignancies of T cells ( 13 , 23 , 104 , 209 ). The direct inhibition of cancer progression by targeting lipid metabolism as well as alleviation of chemo- and immunotherapy response has been demonstrated by various investigations ( 104 , 129 , 209 , 217 ). Considering the demonstrated as well as envisaged impact of lipid metabolism in T-cell malignancies, investigations exploring the connections between hallmark characters with the unambiguous arrangement in lipid metabolism are further warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, molecular modeling analysis suggested that isogingerenone may bind to the fatty acid synthase enzyme, a marker protein in acute lymphoblastic leukemia ( 34 ). It has also been documented that this compound acts preferentially on senescent cells and thus has senolytic activity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%